LIFE+IPNOA mobile prototype for the monitoring of soil N2O emissions from arable crops: first-year results on durum wheat - Bosco, Simona; Volpi, Iride; Nassi o Di Nasso, Nicoletta; Triana, Federico; Roncucci, Neri; Tozzini, Cristiano; Villani, Ricardo; Laville, Patricia; Neri, Simone; Mattei, Federica; Virgili, Giorgio; Nuvoli, Stefania; et al. (Italian Journal of Agronomy, 2015)
Agricultural activities are co-responsible for the emission of the most important greenhouse gases: carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O). Development of methodologies to improve monitoring techniques for N2O are still needful. The LIFE+IPNOA project aims to improve the emissions monitoring of nitrous oxide from agricultural soils and to identify the agricultural practices that can limit N2O production. In order to achieve this objective, both a mobile and a stationary instrument were developed and validated. Several experimental field trials were set up in two different sites investigating the most representative crops of Tuscany (Central Italy), namely durum wheat, maize, sunflower, tomato and faba bean. The field trials were realized in order to test the effect on N2O emissions of key factors: tillage intensity, nitrogen fertiliser rate and irrigation. The field trial on durum wheat was set up in 2013 to test the effect of tillage intensity (minimum and conventional tillage) and nitrogen fertilisation rate (0, 110, 170 kg N ha-1) on soil N2O flux. Monitoring was carried out using the IPNOA mobile prototype. Preliminary results on N2O emissions for the durum wheat growing season showed that mean daily N2O fluxes ranged from –0.13 to 6.43 mg m-2 day-1 and cumulative N2O-N emissions over the period ranged from 827 to 2340 g N2O-N ha-1. Tillage did not affect N2O flux while increasing nitrogen fertilisation rate resulted to significantly increase N2O emissions. The IPNOA mobile prototype performed well during this first year of monitoring, allowing to catch both very low fluxes and peaks on N2O emissions after nitrogen supply, showing a good suitability to the field conditions.